2022
DOI: 10.3390/educsci12020098
|View full text |Cite
|
Sign up to set email alerts
|

Studying Abroad from Home: An Exploration of International Graduate Students’ Perceptions and Experiences of Emergency Remote Teaching

Abstract: The temporary shift from face-to-face instruction to online teaching at North American universities as an alternative solution in response to the COVID-19 pandemic brought significant challenges to international students who had to study abroad from their home countries. Studies on how international students perceive their study-abroad-from-home experiences in such an emergency remote teaching (ERT) context remain scarce. Through the lens of Community of Inquiry and an additional perspective of emotional prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Their hesitation in collaboratively joining online discussions prevented them from building online discourse and reflection, constructing knowledge, and further achieving educational goals via the triggering event, exploration, integration, and resolution cycle (Garrison, 2007). Similar to Dong and Ishige (2022) who noted teaching presence's vital role in shaping students' online learning experiences in an examination of international students' studyabroad-from-home experiences during the pandemic, our findings suggest that improvement in teaching presence is greatly needed to ensure that the international students feel safe learning online, particularly in discourse facilitation (Garrison & Arbaugh, 2007;Garrison et al, 2000). Anderson et al (2001) conceptualized facilitating discourse based on how students are engaged in the process of interacting with the information provided in the course materials.…”
Section: Discussionmentioning
confidence: 99%
“…Their hesitation in collaboratively joining online discussions prevented them from building online discourse and reflection, constructing knowledge, and further achieving educational goals via the triggering event, exploration, integration, and resolution cycle (Garrison, 2007). Similar to Dong and Ishige (2022) who noted teaching presence's vital role in shaping students' online learning experiences in an examination of international students' studyabroad-from-home experiences during the pandemic, our findings suggest that improvement in teaching presence is greatly needed to ensure that the international students feel safe learning online, particularly in discourse facilitation (Garrison & Arbaugh, 2007;Garrison et al, 2000). Anderson et al (2001) conceptualized facilitating discourse based on how students are engaged in the process of interacting with the information provided in the course materials.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of technologies in language teaching and learning has been well-recognized among English teachers ( Dong and Ishige, 2022 ). For example, it transforms pedagogy, breaks the limitation of time and space, provides authentic language teaching and learning materials, facilitates communication, reduces students’ anxiety, and enhances their learning motivation ( Yang and Chen, 2007 ; Shadiev and Yang, 2020 ; Huang F. et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different from traditional technology-enhanced teaching contexts where teachers are physically in the classroom and operate technology to assist teaching, ERT requires teachers to teach in the virtual class, deliver teaching and interact with students synchronously. It's reported that more than 1.5 billion university students in about 188 countries have shifted to ERT since the breakout of COVID-19 (Dong and Ishige, 2022). Recently some countries issued policies to implement formal school teaching and universities took measures to help students to return to in-class learning but, in many countries, especially developing countries with large population densities (e.g., China), governments and universities are still taking measures to prevent the potential largescale infection, and thus, university teachers are conducting classroom-based teaching and ERT alternatively.…”
Section: Emergency Remote Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…En general, las universidades chilenas, optaron por la concepción de Educause (institución que se dedica a promover la educación superior a través del uso de la tecnología) de concebir el proceso de virtualización de la docencia como un proceso de enseñanza remota de emergencia, entendiendo esta, epistemológicamente diferente a la educación en línea u otras modalidades de educación a distancia, dado que esta última presenta mayores complejidades y en muchas ocasiones se fundamenta en modelos de enseñanza online y diseño instruccional más complejas, como por ejemplo; ADDIE, ASSURE y OSQAR, mientras el Emergency Remote Teaching (ERT), término propuesto por (Hodges et al,, 2020) y retomado por varios autores (Bárcenas- López, 2022;Dong & Ishige, 2022;Ducasse, 2022;Martins et al,, 2022) entre otros.…”
Section: Las Problemáticasunclassified